Implementasi SOLID dan Optimalisasi Query pada Aplikasi Pencatatan Kemiskinan - Usman, Usman; Widhiarso, Wijang; Rachmadi, Muhammad (Universitas Multi Data Palembang, 2025)
This research aims to improve the efficiency and performance of the poverty recording application at the Communication and Information Office of Musi Banyuasin Regency by implementing SOLID design principles and query optimization techniques. Using a quasi-experimental approach, the study compares the system before and after code refactoring, The analysis results indicates that the application of SOLID principles and optimization techniques resulted in reduced volume of source code and improved code recommendations. This resulting application is more modular, efficient, and easier to maintain.